Research on College Students' Classroom Learning Based on Informatization to Promote English Education System in China - Yanyun Huang; Suyansah Swanto (UK Zhende Publishing Limited, 2023)
English education in the education of future employees will be essential as a means of identifying and developing personal capabilities as well as serving as a catalyst for the complete informatization of society. Intercultural literacy is a secondary goal of English instruction in China; the main goal is for students to become fluent communicators. The advent of informatization has ushered in a period of fast change across many different business sectors and the globe overall. Instruction in the English language receives a significant focus and investment in China. Traditional methods of education are no longer enough to satisfy the requirements that globalization and Chinese culture impose in this technological age. To improve overall academic achievement, standard classroom evaluation practices need to be revised. With the proliferation of information technology, we have high hopes that this article will be able to considerably enhance the performance of English classroom instruction in school classrooms by offering a new method for assessment. To begin, we compile each student's dataset with data on their English education. Following the preprocessing of the dataset with the Hidden Markov Model (HMM) Stemming Algorithm and the application of information technology with the Radial Basis Coherent Deep Neural Network (RBCDNN), the dataset is evaluated for statistical significance with the Panel Unit Test and the Housman test. The effectiveness of this research is evaluated, and the results are compared to those of previous studies. The findings of this investigation are shown in the form of a chart thanks to the origin tool.